Analisis Abnormal Return dan Trading Volume Activity Sebelum dan Sesudah Ex-Dividend Date: Studi Kasus pada Perusahaan High Dividend 20 yang Terdaftar di Bursa Efek Inodnesia Tahun 2023 - Melia; Sahmin Noholo; Muliyani Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine whether or not there are differences in abnormal returns and trading volume activity before and after the ex-dividend date in 20 high dividend companies listed on the Indonesia Stock Exchange in 2023. The type of method used in this research is a quantitative method. The sampling technique used was purposive sampling. There were 20 companies used as samples in the research. Research data taken for 30 days consists of 5 days, 10 days and 15 days before and after the ex-dividend date. The analysis used was the paired sample t-test and the Wilcoxon Signs rank test. Based on the research results, it shows that 1) there is no significant difference in abnormal returns before and after the ex-dividend date in high dividend 20 companies. 2) there is a significant difference in trading volume activity before and after the ex-dividend date in high dividend 20 companies.